Prevalencia de caries de infancia temprana en niños de 2-5 años, revisión bibliográfica (2020)
Early childhood caries is present in children up to 71 months of age, it presents as a fast and destructive process. Objective: To determine the prevalence of early childhood caries in children from 2 to 5 years old through a bibliographic review. Materials and Methods: A bibliographic review based on scientific literature taking into account 40 indexed articles from different years and authors. Articles adapted to the topic were collected. The results were obtained from the articles studied, and the discussion. Results: It was found that 37.5% of the children were free of caries. 47% never brushed their teeth, 43% brushed only once a day, 10% brushed their teeth 2 or more times a day. Associated risk factors were exclusive breastfeeding, bottle feeding, sugary drinks and foods, socioeconomic level and educational level of the parents, vitamin D deficiency, Candida albicans and type of delivery. 80% of caregivers and parents have insufficient knowledge about the oral care that should be given to children. Conclusions: The prevalence of early childhood caries in most of the cases studied was 60%. The associated risk factors are related to exclusive breastfeeding, bottle-feeding, drinks and foods with high sugar consumption, the socioeconomic and educational level of the parents. The ignorance of parents and caregivers influences considerably the appearance of this problem.